Atividades investigativas: laboratório não estruturado na solução de problemas abertos de trabalho e energia - Moreira, Célio Vicente (2015)
In this work, results are presented from the teaching process as well as the learning investigation of the work end energy concepts with students on the first grade of high school, at a public school in the state of Minas Gerais. The results of this qualitative research were interpreted based on a content analysis. The results of this qualitative, investigative research were interpreted by using content analysis. The concept of work was developed from an open problem, based on an everyday situation, allowing for recognition of students’ previous knowledge. The concepts of kinetics energy, gravitational potential energy and elastic potential energy were also developed from an everyday problem, having for solution of the process the use of non-structured laboratories, by use of low-cost materials. Following, the presented results were employed by the students for the formalization and systematization of the developed concepts, complementing each stage by solving simple exercises. It could be identified the appropriation of knowledge of the developed conceits, increase in the interpreting capacity, planning and searching for solutions aimed at problem situations as well as the growth of interpersonal relationship among all students involved in the task. We can believe that this proposal could be developed for the most part of Physics contents found in High School curricular structures.